2008
DOI: 10.1175/2008jcli2222.1
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry of the Indian Ocean Dipole. Part I: Observational Analysis

Abstract: The physical mechanism for the amplitude asymmetry of SST anomalies (SSTA) between the positive and negative phases of the Indian Ocean dipole (IOD) is investigated, using Simple Ocean Data Assimilation (SODA) and NCAR-NCEP data. It is found that a strong negative skewness appears in the IOD east pole (IODE) in the mature phase [September-November (SON)], while the skewness in the IOD west pole is insignificant. Thus, the IOD asymmetry is primarily caused by the negative skewness in IODE.A mixed-layer heat bud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
86
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 38 publications
10
86
1
Order By: Relevance
“…where T and (u, v, w) represent oceanic mixed-layer temperature (MLT) and 3D ocean currents, ρ and C P are the density and specific heat of water, H is MLT depth (derived by ORAS4 ocean reanalysis data), and R represents residual term (Li et al 2002;Hong et al 2008, Su et al 2010, 2014Chen et al 2015).…”
Section: Methodsmentioning
confidence: 99%
“…where T and (u, v, w) represent oceanic mixed-layer temperature (MLT) and 3D ocean currents, ρ and C P are the density and specific heat of water, H is MLT depth (derived by ORAS4 ocean reanalysis data), and R represents residual term (Li et al 2002;Hong et al 2008, Su et al 2010, 2014Chen et al 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Our results suggest that part of the weaker WCI oxycline depth response during negative IOD may be explained by the weaker wind stress anomalies at the STI associated with negative IOD events. This weaker wind amplitude could simply be related to the tendency of negative IOD events to be weaker than their positive counterpart (Saji and Yamagata, 2003;Hong et al, 2008;Cai et al, 2013) or to asymmetries in the spatial patterns of winds associated with the nonlinear response of deep atmospheric convection to SST anomalies of each phase of the IOD. A more precise understanding of this asymmetry would require an in-depth investigation of the processes that control the wind variations at the STI and the thermocline along the WCI in response to positive and negative IOD events.…”
Section: Influence Of the Iod On The Interannual Oxygen Variability Amentioning
confidence: 99%
“…In the following we diagnose the nature of the air-sea feedback process in IODE based on the observational data in the context of the aforementioned two possibilities. Regarding to the first possibility, a key element is to examine the relationship between the SSHA and the subsurface temperature (hereafter Tsub) anomaly, since the thermocline primarily affects the SST through the change of the ocean subsurface temperature and associated vertical temperature advection [Li, 1997;Hong et al, 2008a]. If the negative skewness in IODE is attributed to the thermocline feedback, then the SSH-Tsub relation should be asymmetric too.…”
Section: Diagnosis Of Air-sea Feedback Processesmentioning
confidence: 99%
“…The slope difference between the positive and negative events is even greater than the asymmetry in the SSH-SST relation. The cause of this asymmetric SST-precipitation relation was discussed in Hong et al [2008a], who found that the negative skewness in IODE is partly attributed to the asymmetry of the SST-cloud-radiation (SCR) feedback. For a positive IODE, the negative SCR feedback continues with the increase of warm SSTA.…”
Section: Diagnosis Of Air-sea Feedback Processesmentioning
confidence: 99%